تطوير مادّة المحادثة القائم على الإطار المرجعي الأوروبي المشترك للغات للمبتدئين بمعهد الكافّة الإسلامي تانجيرانج - Ataska, Sabrina Salsabilla; Royani, Ahmad; Alawiyah, N Lalah (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
AbstractThe use of appropriate teaching materials is crucial for creating an effective learning experience, supporting the achievement of educational objectives. One of the issues identified in teaching conversation at the Al-Kaffah Islamic Institute is that the teaching materials provided are not tailored to the students' proficiency levels. The materials used are based on personal efforts rather than being aligned with any reference framework. Therefore, this study aims to measure the effectiveness of structured teaching materials for teaching conversation at the beginner level (A1), based on the Common European Framework of Reference for Languages (CEFR). This research employed a research and development (R&D) method using the ADDIE model, which includes five phases. The researcher utilized a mixed-methods approach combining qualitative and quantitative methodologies. To collect data, the researcher relied on observations, interviews, questionnaires, and tests.This study resulted in the development of a conversation teaching material product titled “Al-Muhadathah Al-Arabiyyah” (Arabic Conversation) based on the CEFR framework for the A1 beginner level. The material includes vocabulary and exercises, expressions, dialogues, and related exercises.The effectiveness of this teaching material was validated through expert evaluations, where the material received substantial ratings ranging between 81% and 100%, categorized as